2010
DOI: 10.3109/02688691003711575
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative stroke following anterior cervical discectomy

Abstract: We describe a case of postoperative stroke in a patient undergoing anterior cervical discectomy caused by a combination of intraoperative retraction of an atherosclerotic carotid vessel and arterial hypotension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 5 publications
1
11
0
3
Order By: Relevance
“…This is the first case of such a complication occurring beyond the immediate perioperative period, and only the fifth reported cerebral infarct attributable to any etiology after ACDF without corpectomy. [ 1 2 9 11 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first case of such a complication occurring beyond the immediate perioperative period, and only the fifth reported cerebral infarct attributable to any etiology after ACDF without corpectomy. [ 1 2 9 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent investigations revealed a wide range of underlying stroke etiologies, including prolonged retraction compressing the carotid artery, a congenitally abnormal Circle of Willis, and hypotension in the setting of atherosclerosis. [ 1 2 9 11 ] We report the case of a 61-year-old man with a history of pulmonary embolism (PE) and atrial fibrillation, who developed delayed stroke 3 days following an ACDF, most likely attributable to severe but asymptomatic and undiagnosed carotid atherosclerosis, vessel manipulation, coagulopathy, and acute dehydration, which collectively precipitated a large watershed infarct.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, during cervical corpectomy or cervical discectomy, prolonged carotid artery retraction has been associated with CVA in a few cases. 3,4,9 Yeh et al 4 reported a case in which an extensive right hemispheric infract occurred 72 hours after anterior cervical corpectomy of C4.…”
Section: Discussionmentioning
confidence: 99%
“…Last, Radhakrishnan et al 9 presented a case of postoperative stroke following anterior cervical discectomy that involved carotid artery manipulation. However, the CVA complication was attributed to intraoperative hypotension, which was believed to be caused by a continuation of antihypertensive medication rather than carotid retraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation